Стойкий оловянный солдатик: сказки / Х. К. Андерсен - Андерсен Ханс Кристиан (Читаем сами, 2012)
Экземпляры: Ф. 8 (20191017) / Инвентарный номер: 43729 / Цена: 94.00 / Сис.шифр: 84 (4) / Авт.знак: А 65 / ГРНТИ: 17.82.93 / ББК: 84(4Дан)